INTEGRASI NILAI KEISLAMAN DALAM PROSES PEMBELAJARAN DI ERA MOOC (E-LEARNING) MELALUI STRATEGI PRE-POST RULES - Cica Wiswanti; Sinurida Yuswana Belaga (Jurnal Pendidikan Islam, 2020)
Advancing times bring new methods and learning strategies. The progress of the times brings new learning methods and strategies. One model of distance learning is MOOC (Massive Open Online Course) or e-learning. E-Learning or electronic learning is a concept of computer-based learning by utilizing web and internet technology. This is done without face-to-face meetings or meetings between educators and students, enough through technology alone. But in Islamic education we also know the term transvering value or etiquette when we encounter educators at the majlis of science. So this concept will be contradictory and irrelevant to the development of the e-learning distance learning process (MOOC) which is based only on virtual encounters.